Implantable network advertising video marketing based on FPGA and Sobel Algorithm - Jiao, Yang (Microprocessors and microsystems, 2021)
Implantable advertising is called implantable marketing. It can also be understood as a soft ad or hidden advertising. Referring to that product or brand and, newspapers, magazines, online games, cell phone messages and other carriers, through scene reproduction of the brand or product, so that the media information, at the same time, they can unknowingly leave the impression on the product and brand, and then to achieve the purpose of marketing. Therefore, the development of the market for the advertising industry is growing to find new ways of advertising to attract people to become the pressing current challenge for advertisers. New trends in various film and television widely implantable advertising, a quiet and peaceful way has entered our views. Through the development of implantable advertising, promotion and new media video advertising for various products to be introduced to the brand message, leading to the market for digital advertising. Thus, in a video advertising system, the function of each ad is the opinion of the numbered requirements. The system must be completed by their contract to meet the requirements of advertising contracts end play count play. Some ads may appear to reduce other costs allocated for a significant number of comments. This article uses the concept of maximizing the utility function of various advertisers, noting that ad placement in the display order and fairness of the terms. Experimental results show that this method has validity and fairness of the whole system and has a great advantage for all advertising.